Unveiling the Post-Pandemic Pedagogical Shift: A Bibliometric Odyssey into Educational Technology Research on the Scopus Database (2020-2023) - Amien, Moch Yusril Rahmatillah; Maksum, Muh. Nur Rochim; Anshori, Ari; Mubarok, Fahmi Ulum Al (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The aim of this research is to map and analyze the development of research on educational technology in publications indexed in Scopus. The method used is bibliometric analysis, which focuses on the study of publications on the topic of "Technology Education" in the Scopus database after the Covid-19 pandemic from 2020 to 2023. The analysis process involves the use of tools such as Excel and R/R Studio. Visual analysis uses VOSviewer to visualize the co-occurrence of keywords and document citations. This study identified 2289 publications relevant to the established criteria. The results show annual growth of -0.18%, peaking in 2021. The United States was the largest contributor to the number of publications, with Universidad De Granada being the most productive affiliate. The most prolific author on technology education is Yunus, M.M. This research provides a comprehensive review of the education literature with recommendations for future research directions. It is hoped that this research will make a valuable contribution to the understanding of educational strategies.